Feng Shui and Business: How Past Traditions Influence Contemporary Businesses - Naguit, Ma. Cristina (The international journal of religion and spirituality in society, 2020)
This is a descriptive and exploratory study on the feng shui practices of local Chinese businessmen in one of the provinces in the Philippines. The aim of this study is to develop a model that describes the feng shui origins, motives, practices, and its effects on business. The results indicate that the older and younger generations of Chinese businessmen were using feng shui at a moderate to a high level. Nine major themes in the use of feng shui and how it affected their businesses also emerged in the study. These were the origin of feng shui belief, purpose of use, the importance and use of dates and time, the foundation of business, physical structures, lucky charms, manpower, and feng shui’s influence on business. On the basis of the interviews conducted, Chinese businessmen will still continue the use of feng shui not only in their personal lives but also in their business because its adoption brought about positive outcomes in their businesses.